Conceptualizing drivers of policy change in agriculture, nutrition, and food security: The kaleidoscope model - Resnick, Danielle; Babu, Suresh Chandra; Haggblade, Steven; Hendriks, Sheryl; Mather, David (International Food Policy Research Institute, 2015)
The current emphasis in the development community on demonstrating policy impact requires a better understanding of national policymaking processes to recognize opportunities for, and limits to, generating policy change. Consequently, this paper introduces an applied framework, named the kaleidoscope model, to analyze drivers of change in the food security arena, with a specific emphasis on agriculture and nutrition policies. Focusing on five key elements of the policy cycle—agenda setting, design, adoption, implementation, and evaluation and reform—the model identifies key variables that define the necessary and sufficient conditions for policy change to occur. These variables were inductively derived through an extensive review of the secondary literature on episodes of policy change in developing countries across a broad range of policy domains related to food security, including agriculture, education, healthcare, nutrition, and social protection.